Study of the shape optimization of a tee guide vane in a ventilation and air-conditioning duct. (15th March 2018) - Gao, Ran; Liu, Kaikai; Li, Angui; Fang, Zhiyu; Yang, Zhigang; Cong, Beihua
Abstract: Because of the significant resistance effect and the energy consumption effect, increasing attention has been paid to the local resistance represented by tees in ventilation and air-conditioning duct systems in recent years. The resistance reduction method involving installation of a guide vane in dividing flow tees in a ventilation and air-conditioning duct is studied. A reasonable position for installing the guide vane is proposed. The form of the guide vane is optimized. The resistance characteristics of the tee are analyzed under different flow velocities and different aspect ratios of the duct. The implementation effect of optimizing a tee is verified through a full-scale experiment. The results show that the resistance reduction rate of the proposed guide vane is 4.3%–263.8% under different flow ratios (5:1–1:3) and different aspect ratios (4:1–1:4) compared with that of a tee without the guide vane. In some cases, the resistance reduction rate exceeds 100%; the mechanism responsible for this phenomenon is also analyzed. The tee with the proposed guide vane reduces deformation of the fluid, the mechanical energy converted to internal energy and turbulent energy dissipation. The study results are verified through a full-scale experiment; the experimental data are in good agreement with the simulated values and the results reported in previous studies. Highlights: A resistance reduction method of a tee guide vane was introduced. The resistance reduction rates were found to be 4.3%–263.8%. A reduction in resistance was verified.